2002
DOI: 10.1590/s0036-46652002000100003
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status in relation to the efficacy of the rhesus-human reassortant, tetravalent rotavirus vaccine (RRV-TV) in infants from Belém, Pará State, Brazil

Abstract: The rhesus-human reassortant, tetravalent rotavirus vaccine (RRV-TV) was licensed for routine use in the United States of America but it was recently withdrawn from the market because of its possible association with intussusception as an adverse event. The protective efficacy of 3 doses of RRV-TV, in its lower-titer (4 x 10(4) pfu/dose) formulation, was evaluated according to the nutritional status of infants who participated in a phase III trial in Belém, Northern Brazil. A moderate protection conferred by R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 10 publications
0
9
0
3
Order By: Relevance
“…Speculation has also included a nonspecific role for malnutrition or a specific micronutrient deficiency. Thus, when evaluating the protective efficacy of the RRV-TV vaccine according to the nutritional status in infants participating in a phase III trial in Peru, a greater efficacy was found among children reaching a weight for age Z score of more than -1 and a height for age Z score of more than -1 compared with children with lower scores [31] . However, in a recent report from different countries in Latin America, vaccine efficacy induced by the human rotavirus vaccine RIX4414 was similar in well-nourished and malnourished infants [32] .…”
Section: Rotavirus Vaccinesmentioning
confidence: 99%
“…Speculation has also included a nonspecific role for malnutrition or a specific micronutrient deficiency. Thus, when evaluating the protective efficacy of the RRV-TV vaccine according to the nutritional status in infants participating in a phase III trial in Peru, a greater efficacy was found among children reaching a weight for age Z score of more than -1 and a height for age Z score of more than -1 compared with children with lower scores [31] . However, in a recent report from different countries in Latin America, vaccine efficacy induced by the human rotavirus vaccine RIX4414 was similar in well-nourished and malnourished infants [32] .…”
Section: Rotavirus Vaccinesmentioning
confidence: 99%
“…Une hypothèse a également inclus le rôle non spécifique de la malnutrition ou d'une carence en un micronutriment spécifique. Lors de l'évaluation de l'efficacité protectrice du vaccin RRV-TV en fonction du statut nutritionnel chez des nourrissons participant à un essai de phase III au Pérou, une efficacité plus élevée a ainsi été observée chez les enfants atteignant un score Z de poids pour l'âge supérieur à -1 et un score Z de taille pour l'âge supérieur à -1 comparativement aux enfants présentant de plus bas scores [31] . Une récente publication provenant de différents pays d'Amérique latine a cependant indiqué que l'efficacité du vaccin anti-rotavirus humain RIX4414 avait été similaire chez des nourrissons correctement nourris ou malnutris [32] .…”
Section: Vaccins Anti-rotavirusunclassified
“…También se consideró especulativamente un papel inespecífico de la desnutrición o una carencia específica de micronutrientes. En consecuencia, cuando se evaluaba la eficacia protectora de la vacuna RRV-TV de acuerdo al estado nutricional en lactantes que participaban en un ensayo de fase 3 en Perú, se halló una mayor eficacia en los niños que alcanzaban una puntuación Z del peso para la edad superior a -1 y una puntuación Z de la talla para la edad superior a -1 en comparación con niños con puntuaciones menores [31] . No obstante, en un trabajo reciente en países diferentes de América Latina, la eficacia vacunal inducida por la vacuna antirotavirus humano, RIX4414, era similar en lactantes nutridos correctamente y en lactantes desnutridos [32] .…”
Section: Vacunas Antirotavirusunclassified